Implementation and evaluation of community participatory oral health program in school children from select rural population in Deshmukhwadi, Pune district - Pranav Shinde; Sahana Hegde Shetiya; Deepti Agarwal (Wolters Kluwer Medknow Publications, 2023)
Introduction: In order to reduce the oral health disparities among school children in rural areas and provide a sustainable program, a pilot project using community health workers was planned. Aim and Objectives: The objectives of the study were to implement and evaluate community participatory oral health promotion and prevention program in school children from select rural population in Deshmukhwadi, Pune district, and also carry out knowledge, attitude and practice survey among health workers and school teachers about oral health. Materials and Methods: One hundred and thirty-nine students, aged 6-13 years, constituted the sample size. The program consisted of oral health education, atraumatic restorative treatment, scaling of teeth with hand scalers, and fortnightly fluoride mouth rinsing. The health workers who were commissioned into medical department by Tata Motors from the same village, after proper training and calibration performed the above-mentioned preventive procedures on children. Results: There was a significant improvement in gingival status (P < 0.001), caries status (P = 0.003), and incipient lesion (P = 0.01) after the program. In the present study, the health workers were successfully trained to provide basic oral care services in rural areas. Furthermore, the knowledge, attitude, and practice regarding oral health which was assessed among the health workers and school teachers improved after 16 months of the program. Conclusions: The community participatory oral health promotion and prevention program showed a significant improvement in the filled and initial lesion surfaces in the primary and permanent dentition and the bleeding sextants. Health workers and school teachers showed improvement in knowledge and practice after the program.